The Dynamics of Immunological Indicants on the Background of Therapy Using Probiotics and Psyllium in Patients with Chronic Pancreatitis after Cholecystectomy - V.I. RUSIN; YE.S. SIRCHAK; N.YU. KURCHAK (Gastroenterologìa, 2014)
The results of complex examination and treatment of 64 patients with chronic pancreatitis after cholecystectomy are given. It is ascertained, that complex therapy with the use of probiotics and psyllium in patients with chronic pancreatitis after cholecystectomy has marked positive effect on dysbiotic changes and immunity indicants (IgA, IgG, IgM, C3, C4) compared to monotherapy with corresponding medications.